Urgensi Pengaturan Pidana Tentang Ngelem yang Mengandung Zat Adiktif Menurut UndangUndang No 35 Tahun 2009 Tentang Narkotika - Irwan Tjatur Pambudi; Setiyono Setiyono; Indrawati Indrawati (MLJ Merdeka Law Journal, 2020)
This study aims to analyze the urgency of the Criminal Regulation concerning Ngelem according to Law Number 35 of 2009 concerning Narcotics. The problem approach used is normative juridical supported by empirical juridical. The data used are primary. Data analysis was performed descriptively qualitatively. The results of the study showed that the application of the law against nuisance users according to Law Number 35 of 2009 concerning Narcotics and Regulation of the Minister of Health of the Republic of Indonesia Number 44 of 2019 concerning changes in the classification of Narcotics in Indonesia cannot be processed by law enforcement officials. This is because it has not yet been regulated about addictive substances in Ngelem content. So it is necessary to make changes to the Law Number 35 the Year 2009 and the Regulation of the Minister of Health of the Republic of Indonesia Number 44 the Year 2019 regarding the change in the classification of Narcotics.DOI: https://doi.org/10.26905/mlj.v1i1.4291.